Modeling and simulation of biodiesel synthesis in fixed bed and packed bed membrane reactors using heterogeneous catalyst: a comparative study - Sajad Omranpour; Afsanehsadat Larimi (Scientific Reports)
Abstract In this study, modeling and simulation of biodiesel synthesis through transesterification of triglyceride (TG) over a heterogeneous catalyst in a packed bed membrane reactor (PBMR) was performed using a solid catalyst and compared with a fixed bed reactor (FBR). The kinetic data for the transesterification reaction of canola oil and methanol in the presence of solid tungstophosphoric acid catalyst was extracted from the published open literature. The effect of reaction temperature, feed flow rate, disproportionation of the reactants, and reactor length on the product performance was investigated. Two-dimensional and heterogeneous modeling was applied to PBMR and the resultant equations were solved by the Matlab software. Moreover, the velocity profile in the membrane reactor was obtained. The results showed the best conditions for this reaction are 180 °C, the molar ratio of methanol to oil equal 15:1, and the input flow rate of 0.5 mL/min. In this condition, a conversion of 99.94% for the TG can be achieved in the PBMR with a length of 86 cm while a length of 2.75 m is required to achieve this conversion of the FBR. Finally, the energy consumption for the production of 8000 ton/y biodiesel in a production plant using the PBMR and the FBR was obtained as is 1313.24 and 1352.44 kW, respectively.